Thermodynamic and kinetic Calculation for the Binding of Nickel (II) with Some Chelating Agents - M. Al-Rufaie, Elham; A. Essa, Majid (Iraqi Journal of Science, 2023)
Chelating agents were used in a chelation therapy to detoxify heavy metals and toxins and convert them to an inactive form which was excreted out of the body. Nickel is one of these toxic heavy metal when presented in a high values over its allowable limit. This work studies the complexation of some amino acid (Glycine, Histidine, and Arginine) with nickel (II) ion and compare the result with complexation of EDTA (the synthesized amino acid) used in the chelation therapy. Our experiment were performed in a phosphate buffer of PH (7.2) and in a different temperature (283, 288,293, 298, 303)K . The results show a high tendency for these amino acid to nickel ion with an equilibrium constant in arrange of [KNi(II)-EDTA(17.2×108) > KNi(II)-Gly(29×106) >KNi(II)-His(9×106) > KNi(II)-Arg(4.57×106)] mol-1.L . The thermodynamic parameter indicate a spontaneous interaction (negative free energy change ΔG°)) and was positive for each of the enthalpy (ΔH0) and entropy (ΔS0) values indicate that the nature of the emotion is a strong hydrophobic and electrostatic forces, and a second order interaction kinetics with a rate constant in a range of [(6,8×10-2), (11.9×10-2), (21×10-2), (21.8×10-2)] M-1.min-1each (EDTA, Arginine, Histidine, Glycine) respectively .